Celestial Mechanics: From the bases of the past to the challenges of the future - De Melo, C. F.; Prado, A. F.B.A.; Macau, E. E.N.; Winter, O. C. [UNESP]; Gomes, V. M. [UNESP] (IOP Publishing, 2015)
This special issue of Journal of Physics: Conference Series brings a set of 31 papers presented in the Brazilian Colloquium on Orbital Dynamics (CBDO), held on December 1 - 5, 2014, in the city of Águas de Lindoia, Brazil. CBDO is a traditional and important scientific meeting in the areas of Theoretical and Applied Celestial Mechanics. The meeting takes place every two years, when researchers from South America and also guests from other continents present their works and discuss the paths trodden by the space sciences.